A coastal reservoir of biodiversity for Upper Pleistocene human populations: palaeoecological investigations in Gorham's Cave (Gibraltar) in the context of the Iberian Peninsula (Quaternary Science Reviews, 2008)
Palaeobotanical (pollen, charcoal) data from Gorham’s Cave reveals a diversified landscape in the Gibraltar region during the Middle (c. 32 560–23 780 year BP) and Upper Palaeolithic (c. 18 440–10 880 BP). Inferred vegetation types include oak, pine, juniper, and mixed woodlands and savannahs, grasslands with heaths, heliophytic matorrals, phreatophytic formations (e.g. riverine forests, wetlands), and thermomediterranean coastal scrub. A revision of palaeoecological data suggests that patches of trees persisted even in northern and continental territories of the Iberian Peninsula during the cold stages of OIS3 and OIS2. However, a southern Mediterranean coastal shelf extending from Gibraltar to Málaga, and probably further north up to Murcia, was unique in its combination of thermo-, meso-, and supramediterranean plant and animal species. Given the composition of these assemblages, this shelf and its adjacent mountains represented a crucial reservoir of biodiversity during the Upper Pleistocene. It is within this physiographically complex context with its diversity of resources where the last Neanderthals extraordinarily survived until c. 24 000 BP, that is over 10 000 years later than the disappearance of Neanderthals from elsewhere in temperate Europe.

Patterns and processes of Late Quaternary environmental change in a montane region of southwestern Europe (Quaternary Science Reviews, 2002)
This paper examines the Late Quaternary (c. 20,300–o505 cal yr BP) environmental history of Siles, a lake situated at 1320 m in the Segura mountains of southern Spain, with the goalof establishing the mechanisms exerting controlon vegetation change. Palaeoecological indicators include pollen, microcharcoal, spores of terrestrial plants, fungi, and non-siliceous algae, and other microfossils. The Siles sequence is shown to be sensitive to climatic change, although the control exerted by climate on vegetation is ultimately shaped by disturbances and species interactions, determining the occurrence of century-scale lags and threshold responses. Biotically induced changes of vegetation are also shown at the intrazonal level of variation. The new sequence is placed in the context of two previous records to postulate a picture of Holocene environmental change for the Segura region. The existence of mid-elevation glacial refugia for a number of temperate and Mediterranean trees is shown. A mid-Holocene phase (c. 7500– 5200 cal yr BP) emerges regionally as the time of maximum forest development and highest lake levels. The early Holocene occurs as a generally dry, pyrophytic period of pine forests, with grassland scrub in high altitudes, and the late Holocene as a period of protracted vegetation sensitivity, with return to development of pine forests, spread of xerophytic communities, and increased ﬁre activity, under the context of dry spells, localized anthropogenic disturbance, and shallowing and desiccation of lakes. Several events described here correlate with established times of abrupt transitions in the climates of northern Europe, the Mediterranean basin, north Africa, and the Sahel

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data